Science and innovation policy for New Zealand - Jaffe, Adam (New Zealand Science Review, 2013)
The ‘Science of Science Policy’ is an interdisciplinary field of scholarly study that seeks to model, measure, and evaluate the interaction of public policies (including funding) and the performance of the science and innovation system. Such study offers insights and findings that can increase the effectiveness of science and innovation policy for New Zealand. New Zealand’s rate of public investment in research is only about two-thirds, and that of business investment in research about one-third of the OECD average. Our low business R&D intensity is not unexpected given our market size, firm size, and industrial composition. Nevertheless, public policy should aim to mitigate barriers to firms’ ability to undertake high-return research investments. As we undertake only 0.2% of the world’s research, most of the knowledge used in New Zealand is created elsewhere, so positioning ourselves to derive maximum benefit from others’ research is likely to have high payoff. The spillover phenomenon should be considered in making decisions about public research support. A re-balancing from competition towards cooperation, and encouraging linkages between research entities and organisations with a commercial orientation will increase the likelihood of spillover benefits. Research output could be increased relatively quickly by increasing the currently low expenditure per researcher, but any sustained increase will require more skilled scientists and engineers. Therefore public financing of research should include a monitored programme of training grants, and immigration policy settings that do not inhibit attracting skilled scientists and engineers. Attraction and retention of research ‘stars’ should be an explicit objective of New Zealand science policy. A culture of innovation requires an attitude that defines success in terms of the global market, not the local market. It requires a social, economic and cultural environment that rewards risktaking and does not see failure as a barrier to undertaking further investment. Policy makers, too, should be willing to take risks, and systematic